Comparatives study of stool antigen test and serology for helicobacter pylori among Nigerian dyspeptic patients-a pilot study (2010)
"OBJECTIVE:The purpose of this study was to compare the stool antigen (SAT) and immunoglobulin G (IgG) serology tests for Helicobacter pylori in dyspeptic patients in Nigeria, and determine their usefulness. METHOD:Forty six patients with dyspepsia and age and sex-matched healthy controls had their blood and stool collected and screened for H. pylori infection using the enzyme linked immunosorbent assay (ELISA) IgG serology and SAT respectively. Prevalence of H. pylori was 67.4% and 78.3%, among dyspeptics and controls respectively ((p = 0.48) with the SAT while the corresponding values for IgG serology were 67.4% and 91.3%, p = 0.005). RESULT:Patients aged > or = 50 years(8) were more positive to SAT (80%), compared with controls (13) which recorded more positivity in the age range 30-39 years (92.9%). The male gender had more positive SAT in patients (n = 15, 75%) but the SAT was more positive among the female controls 22 (84.6%). Controls in the age range < 30 years were more positive to H. pylori IgG while the patients were more positive at = 30 yrs 10 (100%). CONCLUSION:It is concluded that SAT and IgG serology for H. pylori are both useful in diagnosis of the infection, and are fairly comparable in their ability to detect infection, even in area of high endemicity."